Capacity and Level of Service on the Zagreb Bypass - Štefančić, Gordana; Marijan, Dalibor; Kljajić, Slobodan (Promet - Traffic&Transportation, 2012)
As the capital of the Republic of Croatia, Zagreb is certainly the biggest motorway interchange, as well as the origin and destination of a large number of trips. Apart from obvious advantages, road traffic with its sudden development has caused certain undesired consequences as well, out of which the focus is on the traffic network congestion, including reduction of safety level, mainly because of the greater number of traffic accidents most pronounced in the summer months. The morning and afternoon hours see the highest traffic peaks at junctions, first of all at Buzin where long queues of vehicles are formed. In order to solve the problem the capacity and level of service need to be analysed and the attention should be drawn to the possible requirement of implementing measures in order to increase the capacity and the level of service in the corridor of the Zagreb Bypass.